ChemInform Abstract: Hydrazone—Palladium‐Catalyzed Allylic Arylation of Cinnamyloxyphenylboronic Acid Pinacol Esters. Issue 2 (January 2015) - Watanabe, Kohei; Mino, Takashi; Abe, Taichi; Kogure, Taketo; Sakamoto, Masami
Abstract The catalytic system is found to be optimal for the preparation of various 1, 3‐diarylpropene derivatives bearing a phenolic hydroxyl group.